Recuperando la Tierra: Understanding the Legacies of Social Movements through the Entanglement of Home and Urban Housing Landscapes in Costa Rica - Porter, Jennifer (My University, 2019)
In the mid-1980s, Costa Rican housing activists made ‘anti-violence’ a central piece of their platform for housing justice in the country. Through alliances between socialist and feminist organizations, this movement sought to spatialize justice by (1) providing shelter for the urban poor; (2) encouraging the political enfranchisement and empowerment of women and women-headed households; and (3) providing local level infrastructure for addressing and preventing intrafamilial violence through health cooperatives. Through a pro-poor housing subsidy, the bono de vivienda, preferentially given to low-income families, single-mothers, female-headed households, and the women in dual- or male- headed households where there was a suspicion of partner violence, the Costa Rican housing movement of the 1980s reshaped the relationships and power dynamics of both households and urban housing landscapes. In this dissertation, I traverse the entanglements of home and city to better understand the legacies of a social movement. Where geographers and social movement theorists have addressed question of how social movements arise and are organized, and the production of activist subjectivities, I query their impact on cultures of (anti)violence across time. Drawing on six months of fieldwork, in one marginalized urban neighborhood in the San José-Heredia Metropolitan region of Costa Rica built through the hybridized housing-anti-violence movements, I argue that by reorganizing urban space and the socio–political milieu of cities, social movements inform the way subsequent generations define and respond to emergent social, political, and economic violence. Seventeen participants from ten households were recruited for a short-term cohort study including (1) a life history interview, (2) photovoice, and (3) a follow-up interview with participant-produced photos. Visual methods – photovoice and collaborations with local artists – are critical tools for understanding the complex historical place-based practices of gender and community. Participant images collapse past experience, present practices, and future desires to provide a richer analytic frame for understanding the political heritages of social movements. Using these data, the household as an analytic frame, and a combination of critical landscape studies, heritage studies, and feminist care theory, I trace the ways historical social movements inform how subsequent generations frame and respond to contemporary and emerging forms of intrafamilial and economic violence.
Thesis (Ph.D.)--University of Washington, 2018
Keywords: Home and housing; Latin America; Social movements; Urban space; Violence; Geography; Geography